Developing Lahat Local Culture-Based Instructional Narrative Reading Materialsfor Secondary School Students - Nemisis Dahnisah Argasetra; Soni Mirizon; Machdalena Vianty (Makassar State University, 2022)
Abstract. The objective of this study was to develop Lahat local culture-based instructionalnarrative reading materials which are valid, practical, and have potential effect for secondary school students. This study applied development research which was conductedthrough three phases including analysis, design, and evaluation and revision phases. There were five stages of formative evaluation used in the evaluation phase, they are self-evaluation, expert review, one-to-one evaluation, small group evaluation, and field test evaluation. The participants of this study were theninth-grade students of a public junior high school in Lahat Regency, South Sumatera in academic year 2020/2021. The data were obtained using questionnaire and reading comprehension test.In determining the validity and practicality of the developed reading materials, the average score of questionnaires from experts’ judgement (for validity) and questionnaire in one-to-one and small group evaluation (for practically) were used. The results showed that the developed product was valid (average score 3.87) and practical (average score 4.6). The product also had potential effect since the students reached the passing grade score was 70. Keywords: Material Development, Narrative Text, Reading Materials, Lahat-Local-Culture